Sperm IZUMO1 Is Required for Binding Preceding Fusion With Oolemma in Mice and Rats - Matsumura, Takafumi; Noda, Taichi; Satouh, Yuhkoh; Morohoshi, Akane; Yuri, Shunsuke; Ogawa, Masaki; Lu, Yonggang; Isotani, Ayako; Ikawa, Masahito (Frontiers in Cell and Developmental Biology, 2022)
Fertilization occurs as the culmination of multi-step complex processes. First, mammalian spermatozoa undergo the acrosome reaction to become fusion-competent. Then, the acrosome-reacted spermatozoa penetrate the zona pellucida and adhere to and finally fuse with the egg plasma membrane. IZUMO1 is the first sperm protein proven to be essential for sperm-egg fusion in mammals, as Izumo1 knockout mouse spermatozoa adhere to but fail to fuse with the oolemma. However, the IZUMO1 function in other species remains largely unknown. Here, we generated Izumo1 knockout rats by CRISPR/Cas9 and found the male rats were infertile. Unlike in mice, Izumo1 knockout rat spermatozoa failed to bind to the oolemma. Further investigation revealed that the acrosome-intact sperm binding conceals a decreased number of the acrosome-reacted sperm bound to the oolemma in Izumo1 knockout mice. Of note, we could not see any apparent defects in the binding of the acrosome-reacted sperm to the oolemma in the mice lacking recently found fusion-indispensable genes, Fimp, Sof1, Spaca6, or Tmem95. Collectively, our data suggest that IZUMO1 is required for the sperm-oolemma binding prior to fusion at least in rat.